Design and Experiment Study of Ultrasonic Longitudinal-Torsional Compound Consolidation Vibration System for Metal Foil. (31st July 2020) - Zhong, Xiangqiang; Zhang, Benxue; Huang, Weiqing; Di, Zhimin; Fang, Huajie
Abstract : In order to realize the connection for metal foil, a longitudinal-torsional compound consolidation vibration system is proposed, and relative experiments are carried out. Firstly, the structure of longitudinal-torsional compound consolidation vibration system was designed, detailed structural design of the compound piezoelectric transducer and the compound horn in the vibration system was carried out, and torsional vibration analysis of the compound horn with spiral grooves was carried out based on mechanical principle. Secondly, modal calculation and harmonic response analysis of longitudinal-torsional compound consolidation vibration system were carried out, and corresponding vibration mode and harmonic frequency were obtained. The effect of structural parameters for the compound horn on the frequency of the consolidation vibration system was analysed, and structural parameters of the compound horn were optimized. Finally, the prototype was made, and the experimental platform was built to test the amplitude. When the frequency is near 20000 Hz, the resonance is achieved in three directions at the same time, and the resonance frequency is 19800 Hz. Through the frequency-scanning test, the maximum longitudinal amplitude of the consolidation vibration system is 16 μ m, and the maximum torsional amplitudes of X and Y are 7.9 μ m and 8.1 μ m. The longitudinal-torsional compound consolidation vibration system can realize the connection of the same and different metal foils and has broad application prospects.